2020
DOI: 10.1038/s41598-020-65575-z
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Specific Association between Serum Uric Acid and Incident Fundus Arteriosclerosis in Chinese Population: A Retrospective Cross-Sectional Study

Abstract: Elevated levels of serum uric acid (SUA) were considered to be risk factors for cardiovascular disease, it has been found to be associated with increased arteriosclerosis. The aim of this study was to explore the gender specific relationship between SUA and fundus arteriosclerosis in a healthy population. In a retrospective cross-sectional study, 23474 individuals without diabetes and hypertension were included in the present study. SUA levels were cut to four groups as Q1 to Q4, according to the quartiles. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 53 publications
0
10
2
Order By: Relevance
“…In fact, hypertension is a known risk factor of most diseases included in the current study. [16][17][18][19][20] In contrast, RC time was not correlated with age in the current study. Fundus photographs have been used to detect the risk of systemic hypertension and arteriosclerosis in several settings, such as during health checkups.…”
Section: Discussioncontrasting
confidence: 68%
“…In fact, hypertension is a known risk factor of most diseases included in the current study. [16][17][18][19][20] In contrast, RC time was not correlated with age in the current study. Fundus photographs have been used to detect the risk of systemic hypertension and arteriosclerosis in several settings, such as during health checkups.…”
Section: Discussioncontrasting
confidence: 68%
“…To our knowledge, this is the first study to date to assess the associations between SUA trajectory groups and the risk of retinal arteriosclerosis. Although there have been many studies on the prevalence of retinal arteriosclerosis (1,21,47), there are fewer studies reporting on the incidence. Our study found that the incidence of retinal arteriosclerosis in Chinese men was higher than women.…”
Section: Discussionmentioning
confidence: 99%
“…And our study showed that the association between SUA trajectory groups and retinal arteriosclerosis was statistically significant only in men. SUA has been linked to retinal arteriosclerosis in previous cross-sectional analyzes (21). The cross-sectional nature of prior investigations limits the ability to understand the temporal association of serum uric acid with retinal arteriosclerosis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations